Algumas distorções linguísticas em decisões judiciais brasileiras - Pessoa, Daniel (2025)
Over the course of more than 20 years of practicing Popular Advocacy in Brazil, I have observed court decisions in which textual statements were made about the parties' speeches that I considered to be linguistically unfeasible. The exploratory and qualitative research, with slight quantitative touches, was developed with the aim of offering descriptions of the phenomenon in order to formulate some plausible categories for the linguistic distortions observed. In accordance with Francisco Varela's (1995) perspective on the Sciences and Technologies of Cognition, I classified the object of study as multidisciplinary, so I produced a methodological composition centered on critical discourse analysis, with some elements of participant observation, which made it possible to integrate some levels of complexity into the investigations. As results and conclusions, I have proposed some categories of linguistic distortions operated in relation to the discourses of the parties in the judicial decision of the Brazilian judiciary, according to the sections of the research and the delimitations made.